Do climate variations explain bilateral migration? A gravity model analysis - Andreas Backhaus; Inmaculada Martínez-Zarzoso; Chris Muris (IZA Journal of Migration, 2015)
This paper investigates to what extent international migration can be explained by climatic variations. A gravity model of migration augmented with average temperature and precipitation in the country of origin is estimated using a panel data set of 142 sending countries for the period 1995 to 2006. We find two primary results. First, temperature is positively correlated with migration. Second, stronger changes in precipitation are also associated with aligned, but small changes in migration. Both effects are robust to various model modifications. Furthermore, we present initial explorations into the channels relating climate changes with migration via agriculture and internal conflict.
Keywords: F22; Q54; 330; International migration; Climate change; Gravity model; Panel data